PERANCANGAN PERANGKAT LUNAK APLIKASI PENJUALAN BLOWER - Ajen Kananta; Valentio Davinci Putra; Edwin Alexander (LPPM Universitas Bina Sarana Informatika, 2024)
Abstract - This research explores the design of a blower sales application using the Waterfall method. The aim is to create an application that meets functional and non-functional requirements through a structured software development approach. The Waterfall method was chosen to ensure a smooth development process from planning to implementation. The research results indicate that the produced application successfully meets the specified requirements, with well-documented development stages. Although the Waterfall method has limitations in flexibility to changes, the clarity and control it provides make it suitable for this project.